HIDRADENITIS SUPPURATIVA: SURGICAL TREATMENT WITH LATISSIMUS DORSI MUSCLE FLAP - Castellani, Laurinda; Portella, Jessica Ponte; Matthes, Gustavo Zucca (Mastology, 2019)
The authors present a case report of a 53-year-old female patient who was admitted to the mastology and breast reconstruction sector, at Barretos Cancer Hospital, in 2018, to treat an invasive ductal carcinoma in the right breast. At admission, the patient complained of hidradenitis in the armpits and groin area, with no previous success with clinical or surgical treatment. Hidradenitis is a disease in which there is chronic inflammation of the apocrine glands. With this in mind, an extensive resection of the armpit lesion was performed, and the same right armpit incision was utilized for the sectionectomy and radiopharmaceutical-guided sentinel lymph node biopsy. As for the armpit reconstruction, a bilateral latissimus dorsi flap was used, resulting in an improvement of the patient’s quality of life. With this case report, the authors demonstrate that a breast reconstruction technique could be used to treat a disease that so far had no surgical solution that would not result in confining anatomic consequences for the patient.